Plural Governance in Industrial Purchasing - Heide, Jan B. (Journal of Marketing, 2003)
This article examines the phenomenon of plural governance, a firm's simultaneous use of market contracting and vertical integration for the same basic transaction. The author studies two particular aspects of plural governance, namely the conditions that motivate firms to deploy plural governance and the manner in which one governance form influences the other when the two coexist in a joint structure. Drawing on agency theory and information economics, the author develops a set of research hypotheses and tests them empirically in the context of industrial purchasing decisions. The results suggest that the plural governance phenomenon can be understood from the perspective of solving information asymmetry problems between buyers and suppliers. The author discusses the implications of a “make and buy” approach to extant theory of interfirm governance, relationship management, and marketing strategy in business-to-business settings.